A diffusive stage-structured model with a free boundary - Jingfu Zhao; Changming Song; Hongtao Zhang (Boundary Value Problems, 2018)
Abstract In this paper we mainly consider a free boundary problem for a single-species model with stage structure in a radially symmetric setting. In our model, the individuals of a new or invasive species are classified as belonging either to the immature or to the mature cases. We firstly study the asymptotic behavior of the solution to the corresponding initial problem, then obtain a spreading–vanishing dichotomy and give sharp criteria governing spreading and vanishing for the free boundary problem.